AGRICULTURAL WATER MANAGEMENT - Manish Kumar, ed; Manish Kumar, ed (Croatia Intech)
Watermanagement may greatly influence types of crops to be grown farm structure, costs of farm operation, income from and employment.
Watermanagement System Irrigation Drainage
Keywords: Watermanagement System; Irrigation; Drainage